Modernisation of Higher School of Ukraine in modern conditions to form a professional speech specialist philological profile (Pedagogy of Higher and Secondary Education, 2014)
Drozdovа I. P. Modernisation of Higher School of Ukraine in modern conditions to form a professional speech specialist philological profile.This article takes into consideration the problem of professional formation of the non-philological specialists in conditions of the High School modernization in modern conditions of development of Ukrainian society. Author distinguishes the concept of «linguistic professional education» related to the formation of professionally perfect person.
Keywords: education modernization; professional speaking; competence complex; linguistic professional education; personality formation